VARIATION OF THE EARTH TIDE-SEISMICITY COMPLIANCE PARAMETER THE LAST 50 YEARS FOR THE SOUTH HIMALAIA FAULT, NEPAL - Contadakis, M.E.; Arabelos, D.N.; Vergos, G.; Scordilis, E.M.; Spatalas, S.D. (Bulletin of the Geological Society of Greece, 2016)
Based on the results of our studies for the tidal triggering effect on the seismicity of the Hellenic area, we consider the confidence level of earthquake occurrence - tidal period accordance p as an index of tectonic stress criticality for earthquake occurrence. In this paper, by the occasion of the recent catastrophic earthquake of Nepal, we investigate the variation of the index p for the South Himalaia Fault area. The preliminary results indicate positive correlation of the index p with seismicity, for all the tidal periods. We suggest that this compliance parameter p may be used as an additional element for the seismic risk assessment.